Prevalence and risk factors associated with burnout among occupational therapists / Erna Faryza Mohd Poot and Kosulin Lingok - Mohd Poot, Erna Faryza; Lingok, Kosulin (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Occupational therapist (OT) is at risk of developing burnout due to high cognitive demand in job tasks and the complexity of the practice environment. In Malaysia, the prevalence and the extent of burnout levels among OTs remained in question due to no documented scientific evidence being available. This study aimed to examine the prevalence of burnout among OTs in Malaysia and its associated factors. A cross-sectional study was carried out via an online survey using the Malay version of the Copenhagen Burnout Inventory (CBI-M). The findings showed that OTs in Malaysia were vulnerable to burnout conditions with 69.4% reporting at least one burnout condition (n=108) where Greater Personal Burnout (65.7%) followed by Work-related Burnout (62.0%) and Client-related Burnout (52.8%) were reported. The burnout levels were shown to have a significant association with age and years of working experience (p < 0.05). Meanwhile, the Client- related burnout, in particular, was shown to have differences with marital status. In conclusion, interventions and prevention programs related to burnout should be emphasized and executed at all levels of management to promote better occupational wellbeing among OTs in Malaysia.